The Evolution of the Medical System and Health Status in Romania After the Collapse of Communism - Laura Maxim; Corneliu Diaconu; Andrei Maxim (CES Working Papers, 2015)
The purpose of the present paper is to analyse the changes that occurred in the Romanian medical system since the communism's collapse and until nowadays and to determine the evolution of the population's health status during this period. During the last 25 years, the public Romanian healthcare system has been struggling to cope with underfunding. Our results indicate that this fact had a significant influence on both the medical assistance, reflected in physicians' emigration and poor healthcare conditions, especially in rural areas, and on the individuals' health status, Romania being far behind other EU states from this point of view.
Keywords: I11; I15; I18; 330; health status; healthcare system; healthcare expenditures; medical assistance